(untitled) (Contemporary Mathematics, 2024)
The Undeniable Signature Scheme (USS) was first introduced by chaum and van in 1989. The advantage of the (USS) scheme is the signer’s co-operation during the verification process. In this paper, the Discrete Logarithm Problem with Factor Problem (DLFP) is introduced. It’s security and complexity is analyzed. Then, based on (DLFP), a key exchange protocol is given. An undeniable signature scheme based on DLFP over semiring is proposed along with illustration we have also given application of the proposed USS in Mobile Edge Computing (MEC). Then the proposed scheme’s security and complexity is examined.